Principal Academies in Urban Public Schools: A Literature Review and Multifaceted Conceptual Model. Issue 6 (November 2015) - Bell, Jennifer Harper; Taylor, John L.
This article presents a literature review of principal academies in urban public school districts, with an examination of five prototypical academies. Senge's five disciplines of learning organizations and Guskey's optimal mix model for professional development are linked to form the conceptual perspectives guiding the review. The analysis reveals commonalities in the urban academies' organization, conceptual underpinnings, knowledge bases, and functions, with variations centered on contextual factors. We interrelate and link our findings with the perspectives of Senge and Guskey to inform a proposed model for urban public school academies for principals.